2022
DOI: 10.3390/su14053052
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assurance in E-Learning: A Proposal from Accessibility to Sustainability

Abstract: Given the importance of developing and offering accessible education for all, indispensable aspects of education for sustainable development (ESD) are needed. This study addresses that need by proposing a quality self-assessment for virtual education from an accessibility perspective. This proposal is based on previous literature about quality assurance in e-learning that considered accessibility and its application in the field of higher education. The bibliographic review was conducted by following Multivoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 35 publications
(49 reference statements)
3
15
0
Order By: Relevance
“…It is in line with research that recommends job requirements in teacher training (Haddad, 2018). Although, research shows that e-learning is an important part of active learning, and this is in line with research that believes that students use their skills effectively in e-learning (Ariesta, 2019;Timbi-Sisalima et al, 2022).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…It is in line with research that recommends job requirements in teacher training (Haddad, 2018). Although, research shows that e-learning is an important part of active learning, and this is in line with research that believes that students use their skills effectively in e-learning (Ariesta, 2019;Timbi-Sisalima et al, 2022).…”
Section: Discussionsupporting
confidence: 75%
“…In order to improve the quality of education, the main recommendation is to encourage lecturers and students to use e-learning as part of every course. Other research findings also state that the correct use of elearning can improve the quality of learning (Ariesta, 2019;Timbi-Sisalima et al, 2022;Yaniawati, 2013). Other studies have also revealed that e-learning positively impacts students' ease of learning (Kurtz et al, 2014;Rafiee & Abbasian-Naghneh, 2021;Supriyatno et al, 2020).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, the difference lies in the evaluation model used, where Rosiyanti & Faisal used the CIPP evaluation model while this study uses an innovative evaluation model that combines the educational evaluation model with the concept of local wisdom and the decision support system method. Research studies such as Timbi-Sisalima et al [41], Firmansyah et al [42], Naibaho [43], Setiawan & Munajah [44], and Suswanto et al [45] also corroborate the results of this study by showing the results of the quality test of the implementation of e-learning, even though using a different evaluation model.…”
Section: Figure 3 Final Design Of Formative-summative Evaluation Mode...supporting
confidence: 83%
“…Technology plays a crucial part in every aspect of life (Raja & Nagasubramani, 2018;Zafar, 2019). In recent years, Information and Communication Technologies (ICTs) have opened new opportunities in education (Gilakjani, 2017;Timbi-Sisalima et al, 2022;Uerz et al, 2021), allowing teachers and students to implement technology and redesigning the existing education and training systems (Bandyopadhyay et al, 2021;Basak et al, 2018). Education around the world is undergoing fundamental changes in this era of globalization.…”
Section: Introductionmentioning
confidence: 99%